The Impact of Government Policies on Foreign Direct Investment: The Canadian Experience - Globerman, Steven; Shapiro, Daniel M. (Journal of International Business Studies, 1999)
The purpose of this paper is to identify, using the framework of a statistical model, the extent to which policy changes in Canada specifically directed toward inward foreign direct investment (FDI) have influenced both capital outflows to Canada and capital outflows from Canada. The paper adds to the literature concerned with how public policies targeted specifically at FDI have altered capital inflows, and uniquely links such policies to outward direct investment (ODI). We examine specifically the effects of major policy changes toward FDI implemented by the Canadian government over the period 1950-1995. In Canada's case, free-trade agreements (FTA and NAFTA) appear to have significantly increased levels of inward and outward foreign direct investment; however, Canada's attempt to screen FDI via the Foreign Investment Review Agency (FIRA) had no significant effects on either FDI or ODI.